Awareness of healthcare workers regarding the healthcare sector transformation program in Saudi Arabia - Amro K. Bin Abdulrahman; Alanoud Alshalawi; Sultan Saad Alamri; Elsir Abdelmutaal Mohammed (BMC Health Services Research)
Abstract Background Healthcare transformation is a multifaceted process that hinges on the collaborative efforts of various stakeholders. The success of a significant transformational project is contingent upon the readiness and acceptance among the healthcare workers. Aims This study aims to assess the level of understanding and awareness of healthcare workers regarding healthcare transformation, with a specific focus on Vision 2030. Methods A cross-sectional quantitative study was undertaken involving Saudi healthcare workers. The research employed bivariate correlations and multivariate linear regressions for statistical analysis. Survey data were collected from 456 healthcare workers to gauge their perspectives on healthcare transformation. Results The findings reveal a robust correlation between awareness of healthcare transformation and the perceived significance of the transformation. Notably, participation in the planning and execution stages significantly enhances awareness levels. Conversely, a negative correlation is observed between awareness levels and concerns related to job security and other challenges faced by healthcare workers. Conclusion To ensure the success of the national transformation program, decision-makers should actively involve all potential stakeholders, particularly during the planning and execution stages. Reassuring healthcare workers about job security and addressing their concerns are crucial steps in overcoming resistance and fostering the necessary support for healthcare transformation initiatives.